Risk effects of the spread route of mycotoxins - Bíró, Györgyi; Tamás, János; Borbély, János; Mézes, Lili; Hunyadi, Gergely (Acta Agraria Debreceniensis, 2010)
In Hungary the mycotoxin is a great problem, because there are many natural toxins in wheat and maize. These cereals can be found onconsiderable proportion of the country’s sowing area, and they are deterministic food for the population. The direct human and animalutilization of the contaminated cereals mean a serious risk in the food chain. In Hungary’s climate the soil is contaminated with pathogenmoulds, particularly Fusarium species, which increase by respective temperature and moisture content in cereals. The Fusarium candecrease the quality of the wheat in different ways: decrease the germination capability and cause visible discoloration and appearance ofmould, reduces the dry material and nutrient content of the grain. From the toxins produced by the Fusarium genus, the trichotecene (T-2,HT-2, deoxinivalenol, nivalenol, diacetoxyscxirpenol, Fusarenon-X) and the estrogenic zearalenon (F-2) are the most common in Hungary.The fumonisins (FB1, FB2, FB3) first identified in 1988, relatively newly discovered, are also important. Major proportion of mycotoxins in ahealthy organization is metabolized by the enzyme system of liver and intestinal bacteria. The toxicity is reduced or even leaves off.However, more toxic and biologically active compounds can be formed. For the reduction of mycotoxin-contamination several possibilitiesare available in the case of storage, processing and feeding.